Peran Teknologi Informasi Dalam Meningkatkan Efisiensi Operasional Bisnis Internasional - Roida Purba; Hendra Ibrahim (Universitas 45 Surabaya, 2023)
This research discusses the crucial role of Information Technology (IT) in increasing the operational efficiency of international business through a qualitative approach. Using in-depth interviews and content analysis, this research highlights IT's contribution to simplifying operational processes, strengthening communications across geographic locations, and optimizing resource use. The research findings not only identify the benefits of IT, but also investigate the challenges and opportunities that arise in its implementation in the context of global business operations. The qualitative methodology applied provides a deep understanding of the complex dynamics involved. As a valuable guide, this research provides strategic insights for organizations operating in international markets to optimize the role of IT to achieve operational efficiency and increase their competitiveness at the global level.